Students' Attitudes in Science Learning: Comparison Between Public and Private Junior High Schools - Maison, Maison; Kurniawan, Dwi Agus; Zain, Muhammad Sofyan (Journal of Education Reseach and Evaluation, 2021)
Students' negative attitude is a problem that interferes with the science learning process in public and private schools. Students' negative attitude in learning science is a complex problem to solve. The negative attitude shown is that students are disobedient when given assignments and dislike them. It will have an impact on low student learning outcomes. This study aims to determine students' attitudes towards science subjects by comparing private and public schools. The type of research used is a descriptive mixed method. The instrument of this type of quantitative research is in the form of a questionnaire, while the qualitative instrument is an interview sheet for students and teachers of science subjects. The number of samples was 236 students using the purposive sampling technique, while the qualitative samples were eight students and two science teachers. The quantitative analysis technique used is descriptive statistics, and the qualitative analysis technique summarizes the results of the interviews. The result is that students' attitudes towards science subjects in public and private junior high schools are already promising. Based on student attitudes, public schools are categorized as having slightly better attitudes than private schools. The results of interviews with students and teachers can also be revealed that most students have positive attitudes towards science, students who are not positive with actions such as teachers, are active alone when learning activities take place, disturb friends, etc. are at least harmful. Attitudes must be changed in students. The results show that public junior high school students have slightly more positive attitudes than private students.